Financial Performance Measurement Using Solvency Ratio at PT. AKR Corporindo Tbk. 2015-2019 Period - Bella Puspita Rininda; Yuli Fitriyani; Azizah (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This study aims to measure the financial performance of PT AKR Corporindo Tbk's 2015-2019 financial statements by using the solvency ratio. The method in this research is quantitative. The subject in this study is the financial statements of PT AKR Corporindo Tbk in 2015-2019 using the solvency ratio. The results of this study indicate that the assessment of financial performance at PT. AKR Corporindo Tbk, for the debt to asset ratio is considered not good because it exceeds the industry average standard that has been set, the debt to equity ratio is considered healthy even though it exceeds the industry average standard, because large funds are obtained from short-term debt, namely debt business, and the long term debt to equity ratio is also considered good because it is below the industry average standard. The results of this study indicate that the solvency ratio at PT AKR Corporindo Tbk has decreased and increased according to industry standards.